Comparison of Doxorubicin Plus Docetaxel Neoadjuvant Chemotherapy with Doxorubicin Plus Vinorelbine in Primary Breast Cancer - Gwak, Geumhee; Kim, Ji-Young; Park, Keongmee; Shin, Young Joo; Cho, Hyunjin; Park, Sung Jin; Yang, Geun Ho; Bae, Byung Noe; Kim, Ki Whan; Han, Sehwan (Journal of breast cancer, 2011)
This study was performed to compare the therapeutic efficacy and toxicity of doxorubicin plus docetaxel neoadjuvant chemotherapy (NC) with doxorubicin plus vinorelbine NC. Fifty-three patients underwent 4 cycles of NC consisted of intravenous injection of doxorubicin (50 mg/m(2)) plus docetaxel (75 mg/m(2)) administered every 3 weeks (AD), while 49 patients underwent 4 cycles of NC consisted of intravenous injection of doxorubicin (50 mg/m(2)) and vinorelbine (25 mg/m(2)) administered every 3 weeks (AN). Response rate and treatment-related toxicities were analyzed by administered chemotherapeutics. Response to NC was also analyzed according to clinicobiological characteristics of the primary tumors. Clinical response was observed in 66% with AN and 81.6% with AD chemotherapy. A complete pathologic response (pCR) was confirmed in 6 patients (11.3%) with AN and in 7 patients (14.3%) with AD after the surgery. Response rate was significantly higher in AD compared with AN (p=0.038), but there was no significant difference between the two group regard to pCR rate. Breast conserving surgery (BCS) was performed in 35.8% of AN group, whereas 20 patients (40.8%) of AD group underwent BCS. The patients with HER2-amplified tumor showed significantly increased response to both types of NC. Pathologic complete response was confirmed in 9 (39.1%) out of 23 HER2-amplified tumors, whereas only 4 (5.1%) of 79 HER2-nonamplified tumors showed pathologic complete response. Febrile neutropenia occurred in 22.6% of total 212 cycles in AN and 38.8% of total 196 cycles in AD. Grade 3/4 neutropenia was observed in 39.6% in AN and 43.9% in AD. Grade 3 mucositis was observed in 26.4% with AN and in 40.8% with AD. There was no significant increase of pCR by AD compared with AN. Long-term follow-up results of our study indicate that clinical outcome after NC was significantly associated with initial response to NC regardless of therapeutic regimens.